2011
DOI: 10.1128/jb.00378-11
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Attachment of Vibrio cholerae Mediated by the Toxin-Coregulated Pilus in the Infant Mouse Model

Abstract: Colonization of the human small intestine by Vibrio cholerae is an essential step in pathogenesis that requires the type IV toxin-coregulated pilus (TCP). To date, three functions of TCP have been characterized: it serves as the CTX⌽ receptor, secretes the colonization factor TcpF, and functions in microcolony formation by mediating bacterium-bacterium interactions. Although type IV pili in other pathogenic bacteria have been characterized as playing a major role in attachment to epithelial cells, there are ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 39 publications
2
69
0
Order By: Relevance
“…V. cholerae cells were visualized in sections of fixed zebrafish by fluorescence microscopy using a primary polyclonal antibody directed against V. cholerae and a secondary monoclonal antibody carrying the fluorescent tag. The contact between V. cholerae and the intestinal epithelial surface observed in zebrafish very closely resembles the interaction between V. cholerae and the epithelial surface observed in mammalian models (36,37).…”
Section: Resultsmentioning
confidence: 69%
“…V. cholerae cells were visualized in sections of fixed zebrafish by fluorescence microscopy using a primary polyclonal antibody directed against V. cholerae and a secondary monoclonal antibody carrying the fluorescent tag. The contact between V. cholerae and the intestinal epithelial surface observed in zebrafish very closely resembles the interaction between V. cholerae and the epithelial surface observed in mammalian models (36,37).…”
Section: Resultsmentioning
confidence: 69%
“…In E. coli, remodeling of bundled pili into even thicker bundles via the action of the retraction ATPase BfpF was required for microcolony dispersal (232), suggesting that the particular mode of pilus-pilus interaction affects the subsequent behavior of bacteria. A recent study of V. cholerae binding to intestinal epithelia revealed that aggregates of T4P enveloped the bacteria, potentially protecting them during the infection process (238). In S. Typhi, bundling of pili is negatively controlled by expression of one of two variants of the minor pilin, PilV (note that this is a different component than the Neisseria protein of the same name).…”
Section: Adherence and Aggregationmentioning
confidence: 99%
“…V. cholerae uses its OmpU outer membrane protein to adhere to the brush border of fully differentiated Caco-2 cells (410). The type IV TCP of V. cholerae has three functions: it acts as a receptor for CTXPhi, the lysogenic filamentous bacteriophage that carries the CT genes in epidemic V. cholerae strains; it secretes the colonization factor TcpF and contributes to microcolony formation by mediating bacterium-bacterium interactions; and it acts as an attachment factor for binding to fully differentiated Caco-2 cells, since attachment was defective in mutants lacking TCP compared to in the wild type (411).…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%